2011
DOI: 10.1063/1.3629507
|View full text |Cite
|
Sign up to set email alerts
|

The Largest Pulsar Glitch and the Universality of Glitch Behavior

Abstract: Large pulsar glitches seem to be common to all radio pulsars and to exhibit a universal behaviour connecting the rate of occurrence, event size and interglitch relaxation that can be explained if the glitches are due to angular momentum exchange in the neutron star. This has implications for the energy dissipation rate. The large timing excursions observed in SGRs are not similar to the pulsar glitches. The one glitch observed in an AXP is very similar to pulsar glitches and demonstrates that typical neutron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…It was shown that Vela pulsar, J0537-6910 and J1341-6220 show a quasiperiodic glitch pattern [15]. Vela alone was reported to have quasiregularly pattern [18], and a linear glitch pattern was also reported for Vela and J0537-6910 depicting also strong elasticity of the objects [12]. This corroborated the report that Vela and J0537-6910 have particular glitching behaviours or pattern and that such pattern may be shared by most Vela-like pulsars [11].…”
supporting
confidence: 80%
See 1 more Smart Citation
“…It was shown that Vela pulsar, J0537-6910 and J1341-6220 show a quasiperiodic glitch pattern [15]. Vela alone was reported to have quasiregularly pattern [18], and a linear glitch pattern was also reported for Vela and J0537-6910 depicting also strong elasticity of the objects [12]. This corroborated the report that Vela and J0537-6910 have particular glitching behaviours or pattern and that such pattern may be shared by most Vela-like pulsars [11].…”
supporting
confidence: 80%
“…11, 12, 15, 19, 23]. Alpar reported only that of Vela [18], and PSR1341-6220 was reported to have quasi-regular pattern [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Considering current experimental and theoretical constraints on the dense-matter equation of state, we find that the crustal superfluid does not carry enough angular momentum to explain Vela pulsar glitches. Even if crustal entrainment is ignored, the standard vortex-mediated glitch scenario has been challenged by the observation in 2010 of a huge glitch in PSR 2334+6 from which the following constraint was inferred: I crust /I ≥ 9.4% [84]. These observations suggest that the neutron superfluid in the core of a neutron star contributes to glitches [85].…”
Section: Discussionmentioning
confidence: 99%